EFEK ANTIINFLAMASI KOMBINASI ASTAXANTHIN DENGAN VITAMIN E TERHADAP JUMLAH INTERLEUKIN-6 (IL-6) Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan - Nafla Aqilah Salma; Sampurna (Jurnal Riset Multidisiplin Edukasi, 2026)
Chronic inflammation is a major trigger for various degenerative diseases, with interleukin-6 (IL-6) as an important indicator in assessing the level of inflammation. Astaxanthin and vitamin E are known as powerful antioxidants with potential anti-inflammatory effects, but the synergistic effects of the two have not been widely explored. This study aims to determine whether the combination of astaxanthin and vitamin E can significantly reduce IL-6 levels in male Wistar rats induced with carrageenan. The study used an experimental design with a post-test only control group design, involving three groups: KN (normal group fed a standard diet), KS (diseased group with 1% carrageenan induction), and KP (fed a combination of 0.72 mg/kgBW astaxanthin and 24.1 mg/kgBW vitamin E). Data were obtained from plasma IL-6 level measurements using the ELISA method 24 hours after carrageenan induction, followed by data analysis using normality and homogeneity tests, One Way ANOVA, and continued with the Tamhanes Post Hoc test. The treatment group experienced a significant decrease in mean IL-6 levels, namely 58.67 pg/mL compared to the disease group, which was 98.83 pg/mL, indicating the anti-inflammatory effect of the combination. From the results of this study, it can be concluded that there is an anti-inflammatory effect of the combination of astaxanthin and vitamin E on Interleukin-6 (IL-6) levels in male Wistar rats induced with carrageenan.